A novel sphingosylphosphorylcholine and sphingosine-1-phosphate receptor 1 antagonist, KRO-105714, for alleviating atopic dermatitis - Sae-Bom Yoon; Chang Hoon Lee; Hyun Young Kim; Daeyoung Jeong; Moon Kook Jeon; Sun-A Cho; Kwangmi Kim; Taeho Lee; Jung Yoon Yang; Young-Dae Gong; Heeyeong Cho (BMC, 2020)
Abstract Background Atopic dermatitis (eczema) is a type of inflammation of the skin, which presents with itchy, red, swollen, and cracked skin. The high global incidence of atopic dermatitis makes it one of the major skin diseases threatening public health. Sphingosylphosphorylcholine (SPC) and sphingosine-1-phosphate (S1P) act as pro-inflammatory mediators, as an angiogenesis factor and a mitogen in skin fibroblasts, respectively, both of which are important biological responses to atopic dermatitis. The SPC level is known to be elevated in atopic dermatitis, resulting from abnormal expression of sphingomyelin (SM) deacylase, accompanied by a deficiency in ceramide. Also, S1P and its receptor, sphingosine-1-phosphate receptor 1 (S1P1) are important targets in treating atopic dermatitis. Results In this study, we found a novel antagonist of SPC and S1P1, KRO-105714, by screening 10,000 compounds. To screen the compounds, we used an SPC-induced cell proliferation assay based on a high-throughput screening (HTS) system and a human S1P1 protein-based [35S]-GTPγS binding assay. In addition, we confirmed the inhibitory effects of KRO-105714 on atopic dermatitis through related cell-based assays, including a tube formation assay, a cell migration assay, and an ELISA assay on inflammatory cytokines. Finally, we confirmed that KRO-105714 alleviates atopic dermatitis symptoms in a series of mouse models. Conclusions Taken together, our data suggest that SPC and S1P1 antagonist KRO-105714 has the potential to alleviate atopic dermatitis.